2012
DOI: 10.1161/circheartfailure.112.966622
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase p110α Is a Master Regulator of Exercise-Induced Cardioprotection and PI3K Gene Therapy Rescues Cardiac Dysfunction

Abstract: Background— Numerous molecular and biochemical changes have been linked with the cardioprotective effects of exercise, including increases in antioxidant enzymes, heat shock proteins, and regulators of cardiac myocyte proliferation. However, a master regulator of exercise-induced protection has yet to be identified. Here, we assess whether phosphoinositide 3-kinase (PI3K) p110α is essential for mediating exercise-induced cardioprotection, and if so, whether its activation independent of exercise ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 51 publications
6
99
0
Order By: Relevance
“…It has further been suggested that exercise enhanced PI3K (p110a) activity could delay or prevent progression of dilated and hypertrophic cardiomyopathy (McMullen et al, 2007). Finally, a recent study has described that PI3K(p110a) gene therapy reduced cardiac dysfunction (Weeks et al, 2012). Our studies here show that reduction of Vcl levels in cardiac myocytes reduced PI3K activation, and inhibited autophagic and apoptotic signaling, compared to control cells with normal Vcl expression.…”
Section: Novel Role Of Vcl In Pi3k/akt Signalingsupporting
confidence: 64%
“…It has further been suggested that exercise enhanced PI3K (p110a) activity could delay or prevent progression of dilated and hypertrophic cardiomyopathy (McMullen et al, 2007). Finally, a recent study has described that PI3K(p110a) gene therapy reduced cardiac dysfunction (Weeks et al, 2012). Our studies here show that reduction of Vcl levels in cardiac myocytes reduced PI3K activation, and inhibited autophagic and apoptotic signaling, compared to control cells with normal Vcl expression.…”
Section: Novel Role Of Vcl In Pi3k/akt Signalingsupporting
confidence: 64%
“…We recently generated a recombinant adeno-associated viral (rAAV) vector containing caPI3K that selectively transduced cardiac muscle, minimising the concern of PI3K's tumorigenic potential in other cell types [48]. rAAV6-caPI3K improved cardiac function in a mouse model of pressure overload and AAV-based therapies have entered clinical trials in heart failure patients [49,50]. Future studies will be required to assess whether rAAV6-caPI3K can improve function in a setting of diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an increased activation in the combined MI/exercise group might be explained by the different pathways induced by the different hypertrophy triggers. In fact, physiological stimuli like exercise act via IGF-I/PI3K p110␣ (10,47,81), whereas a pathological stimulus like MI rather activates PI3K p110␥ (57,59,63). The presence of both stimuli in the MI-runner group might then lead to a complex cross-talk wherein these two signaling pathways interfere.…”
Section: H355 Exercise Limits Post-mi Scar Thinningmentioning
confidence: 99%